Marketing communication strategy for creative talents service providers a case study of an online marketplace in Indonesia - Dwityas, Nindyta Aisyah; Briandana, Rizki; Marta, Rustono Farady; Aliagan, Isiaka Zubair (Association for Scientific Computing Electrical and Engineering (ASCEE), 2022)
This study aims to analyze the marketing communication strategy one of the creative talents service provider marketplace in Indonesia, namely Sociabuzz. The development of the marketplace business is not only limited to product sales, but has also begun to expand into the service sector. The marketplace is also open to creative industries to get customers or markets. The concept used in this research is Marketing Communication Strategy and Online Marketplace as one of the Sharing Economy Business Platforms. The research method used is a case study by conducting structured interviews with Strategic Planner, and Campaign and Marketing Executive of the organization. The results show the principles of sharing economy, especially those related to the principles of partnership, empowerment, and collaborative efforts, not only underlie Sociabuzz's business processes and strategies, but also form the basis of their marketing communication strategies, which are contained eight important stages: situation analysis, identification of advantages, formulation of big ideas for campaigns, targeting, determining communication objectives, budgeting, campaign implementation, and campaign evaluation.